Accommodation Paralysis after Pheniramine Maleate Injection: A Case Report. (December 2013) - Bingol Kiziltunc, Pinar; Atilla, Huban; Yalcindag, F. Nilufer
Abstract We present a case in which Gilbert syndrome was diagnosed following a neuro-ophthalmic complaint. Adverse effects of drugs as well as various systemic, neurological, and local ocular pathologies can cause accommodative insufficiency and loss of accommodation. A 29-year-old man was admitted to an ophthalmology department with blurred vision and diagnosed as suffering from acute accommodation paralysis. He had a history of being given a pheniramine maleate injection for pruritus 20 days previously. Symptoms began immediately following the injection. After systemic evaluation and laboratory tests, he was diagnosed as having Gilbert syndrome. His complaints and symptoms recovered in approximately a further 10 days. Metabolism of pheniramine maleate can be impaired in Gilbert syndrome and anticholinergic effects can cause accommodation paralysis.